AUDITOR INDEPENDENCE, AUDITOR ETHICS, AUDITOR EXPERIENCE, AND DUE PROFESSIONAL CARE ON AUDIT QUALITY - Kenny Ardillah; Robby Chandra (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Kristen Indonesia Paulus, 2022)
Public accountants are exceptionally important to give certainty to clients that the financial statements introduced by the organization can be trusted, but the risk of misstatement will in any case exist despite the fact that it has been evaluated by a Public Accounting Firm. This study expects to analyze the components that influence audit quality that can lessen the risk of misstatement in the presentation of financial statements, specifically auditor independence, auditor ethics, auditor experience, and due professional care. The subject in this study were employees who worked as auditors at the Tangerang’s Public Accounting Firms. This type of research is a causal study with a convenience sampling method. The research period was completed during the Coronavirus pandemic from March to June 2020. The hypothesis test method used in this research is multiple regression analysis. The results of this study are auditor independence does not affect audit quality, auditor ethics does not affect audit quality, auditor experience has positive effect on audit quality, and due professional care has positive effect on audit quality. This research is expected to be a reference in making decisions by auditors based on audit considerations possessed by an auditor to improve audit quality, especially from the experience and due professional care of the auditor.